The Influence Of Budget Participation On Managerial Performance: The Role Of Organizational Commitment And Delegation Of Authority As Intervening Variables - Safruddin, Safruddin; Gunarsih, Tri; Awaluddin, Murtiadi (SEAN Institute, 2024)
This study aims to examine the influence of budget participation on managerial performance, with the roles of organizational commitment and delegation of authority as intervening variables. Three research hypotheses were tested using SEM PLS. The population in this study consists of all officials, including directors, marketing and registration managers, learning and examination service managers, registration, examination & learning coordinators, and administrative staff within the Open University, particularly in regional offices in Indonesia. A sample of 147 was tested. The results support two hypotheses: (i) Budget participation has a significant effect on managerial performance, and (ii) Budget participation significantly affects managerial performance through organizational commitment. However, the hypothesis testing the effect of budget participation on managerial performance through delegation of authority was not supported. This study emphasizes the importance of budget participation and organizational commitment in enhancing managerial performance, as well as providing insights into factors that do not have an impact in this context.